Emotional intelligence and academic achievement: the moderating influence of age , intrinsic and extrinsic motivation (2010)
The study examined the moderating influence of emotional intelligence, age and academic motivation on academic achievement of secondary school students. The study adopted a survey research design. The participants in the study were 1563 (male=826, female=737) secondary school students from Oyo state, Nigeria. Their age ranged between 12 years and 17 years with mean age 0f 15.96 years. Two valid and reliable instruments were used to assess emotional intelligence and academic motivation while achievement test on English Language and Mathematics were used as a measure of academic achievement. Descriptive statistics, Pearson’s product moment correlation and hierarchical regression were used to analyse the data. The result revealed that the Emotional Intelligence, Age and Academic Motivation were potent predictors mildly associated to academic achievement. The study has implications for the curriculum developers to integrate emotional intelligence into the school curriculum of secondary school. That teachers, counseling and educational psychologists should encourage the development of a strong achievement motivation in the students through the provision of appropriate counseling intervention programmes and enabling environment. By so doing, the academic performance of the students could be improved barring all other teaching-learning obstacles.